1981
DOI: 10.1103/physrevd.23.1567
|View full text |Cite
|
Sign up to set email alerts
|

CPviolation inB-meson decays

Abstract: The pattern of CP violation in the bottom sector is discussed. We introduce general techniques to expose new CPviolating effects in the cascade decays of B mesons. In the Kobayashi-Maskawa (KM) model, the CP asymmetries so obtained range from 2-20 % for plausible values of the model parameters. This is to be compared with the small effects, of order 10-3-10-4, previously exhibited within this model. Effects of this size should be observable in upcoming experiments. Our approach stresses the on-shell transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
236
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(239 citation statements)
references
References 17 publications
3
236
0
Order By: Relevance
“…Recently, BaBar [1] and Belle [2] have observed large time-dependent CP asymmetries in the neutral B-meson system [3]. Decay modes of neutral B mesons to final states containing charmonia were used for these measurements due to their clean experimental signatures and straightforward theoretical interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, BaBar [1] and Belle [2] have observed large time-dependent CP asymmetries in the neutral B-meson system [3]. Decay modes of neutral B mesons to final states containing charmonia were used for these measurements due to their clean experimental signatures and straightforward theoretical interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…We examined these possibilities, and concluded that the subtle excess of the branching ratio mainly comes from (1), and the effects from (2) are very small.…”
Section: Resultsmentioning
confidence: 99%
“…The standard model (SM) predicts large CP violation in B decays [1,2] and they have been verified in B → J/ψK s [3,4], B → ππ [5,6], and B → DK [7] decays. The quest of high energy physics has always been to search for the most fundamental theory.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is a small effect in general, CP violation can be relatively large in some decay channels of B and B s mesons [3][4][5][6]. In fact, large CP violation has been confirmed in some two-body decay channel of the B and B s meson, such as B ± → D CP(+1) π ± [7], B ± → ρ 0 K ± [8], B ± → ρ 0 K * (892) ± [9], B ± → f 0 (1370)π ± [10], B 0 → ρ − K + [11], and B s → π + K − [12,13].…”
Section: Introductionmentioning
confidence: 99%